2014
DOI: 10.1177/2150131914538455
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Patient Ratings of Medical Home Domains Among Adults With Diabetes

Abstract: This study demonstrates that not all PCMH clinics are alike and that these differences can possibly affect patient perceptions of their care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…Four studies reported a slightly higher level of satisfaction among patients regarding the care they received from their physician following implementation of the Medical Home model (Solberg et al 2011;Carrillo et al 2014;Hall et al 2014;Heyworth et al 2014). One study reported an improvement in patient satisfaction after 12 (Reid et al 2009) and 24 months of PCMH care; however, this improvement in doctor-patient interaction diminished over time.…”
Section: Patient-provider Relationshipmentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies reported a slightly higher level of satisfaction among patients regarding the care they received from their physician following implementation of the Medical Home model (Solberg et al 2011;Carrillo et al 2014;Hall et al 2014;Heyworth et al 2014). One study reported an improvement in patient satisfaction after 12 (Reid et al 2009) and 24 months of PCMH care; however, this improvement in doctor-patient interaction diminished over time.…”
Section: Patient-provider Relationshipmentioning
confidence: 99%
“…Two studies demonstrated an increase in patient satisfaction with office staff within the PCMH model compared with the traditional model of care (Christensen et al 2013;Hall et al 2014). Other researchers described a high level of positive patient experience in the PCMH when it came to practice staff providing respectful, helpful care (Cook et al 2015(Cook et al , 2016 and in terms of friendly, helpful staff (Kennedy et al 2015).…”
Section: Patient-practice Relationshipmentioning
confidence: 99%
See 3 more Smart Citations